Investigations into the role of mast cell mediated effects on the intestinal epithelial barrier in vitro : implications for the pathogenesis of irritable bowel syndrome - Wilcz-Villega, Ewa (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2013)
Irritable bowel syndrome (IBS) is a highly prevalent functional bowel disorder characterised by abdominal pain or discomfort and associated with altered bowel habit, abdominal bloating and disturbed defecation. The aetiology of IBS is multifactorial. Increasing evidence has implicated impaired barrier function and immune activation in this condition.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin